Prevalence of Norovirus in produce sold at retail in the United Kingdom. (June 2019) - Cook, Nigel; Williams, Luminita; D'Agostino, Martin
Abstract: To acquire data on contamination with Norovirus in berry fruit and salad vegetables in the United Kingdom, one thousand one hundred and fifty two samples of fresh produce sold at retail in the UK were analysed for Norovirus. Of 568 samples of lettuce, 30 (5.3%) were Norovirus-positive. Most (24/30) lettuce samples which tested positive for Norovirus were grown in the UK and 19 of those 24 samples contained NoV GI. Seven/310 (2.3%) samples of fresh raspberries were Norovirus-positive. Most (6/7) of the positively-testing fresh raspberry samples were imported, but no predominance of a genogroup, or any seasonality, was observed. Ten/274 (3.6%) samples of frozen raspberries were Norovirus-positive. The country of origin of the positively-testing frozen raspberry samples was not identified in most (7/10) instances. The collected data add to the currently limited body of prevalence information on Norovirus in fresh produce, and indicate the need for implementation of effective food safety management of foodborne viruses. Highlights: Fresh / frozen raspberries and lettuce were sampled from UK retail outlets over a 13 months, and tested for Norovirus. 5.3% of lettuce, 2.3% of fresh raspberry, and 3.6% of frozen raspberry samples were Norovirus-positive. The data raises whether food safety management systems are being effectively implemented in these food supply chains.